1991
DOI: 10.1111/j.1651-2227.1991.tb11863.x
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological and Precipitating Factors for Childhood Enuresis

Abstract: Aetiological factors for enuresis in 68 nightwetting (NW) and 73 day and mixed day and nightwetting (DW/MW) children were examined against a random sample of 142 control children drawn from a population of 3,375 seven-year-old children. Twenty-six variables concerning age, sex, social background, life changes, familial and perinatal history, development, growth, neurological damage, psychic structure and urinary tract disorders were included in the logistic regression analysis. The familial influence on enures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 23 publications
7
42
0
5
Order By: Relevance
“…Previous studies on the ALSPAC population have shown that it is important to consider not only those children whose bedwetting meets DSM-IV criteria, but also those with less frequent bedwetting due to a number of adverse psychological outcomes in this group (Joinson et al 2007b). Another study reported evidence for neurological impairments in children whose bedwetting did not meet DSM-IV criteria (Jarvelin et al 1991). It is notable that we found a strong relationship between the trajectory groups and the frequency of bedwetting, with the rates of bedwetting twice or more per week being much higher within the persistent wetting group and very low in the relapsing group.…”
Section: Limitationssupporting
confidence: 44%
“…Previous studies on the ALSPAC population have shown that it is important to consider not only those children whose bedwetting meets DSM-IV criteria, but also those with less frequent bedwetting due to a number of adverse psychological outcomes in this group (Joinson et al 2007b). Another study reported evidence for neurological impairments in children whose bedwetting did not meet DSM-IV criteria (Jarvelin et al 1991). It is notable that we found a strong relationship between the trajectory groups and the frequency of bedwetting, with the rates of bedwetting twice or more per week being much higher within the persistent wetting group and very low in the relapsing group.…”
Section: Limitationssupporting
confidence: 44%
“…Это наблюдение подчеркива-ет роль общей структурно-функциональной незрелости в его патогенезе [23][24][25]. Как показали исследования, проведенные у детей с энурезом, чаще наблюдается задержка становления двигательных и речевых навыков [26,27]. Гипотеза о различии в темпах созревания цен-тральной нервной системы у пациентов с первичным энурезом, по сравнению со здоровыми детьми, под-тверждается результатами нейрофизиологических исследований [28][29][30].…”
Section: задержка структурно-функционального созреванияunclassified
“…Disrupting experiences for the child in the early years appear to enhance the exposure to nocturnal enuresis. Traumatic events, that the child is exposed to, such as parents separation or divorce 18 during a sensitive phase in the development of bladder control (around the age two to three years), have been found to be correlated to the later development of nocturnal enuresis. This has been referred to as the "interrupted learning theory."…”
Section: Enuresis: a Common Issue Among Children And Adolescentsmentioning
confidence: 99%